Research on influences of groundwater salinity and flow velocity on artificial frozen wall. (May 2022) - Qin, Biao; Rui, Dahu; Ji, Mingchang; Chen, Xiongzhi; Wang, Shuren
Abstract: Groundwater flow has a negative impact on the artificial freezing project, especially when the salt content of the groundwater is high, it will change the thermophysical properties, which isn't conducive to the formation of the frozen wall. In this paper, the changes in temperature and seepage fields during the formation of frozen wall under the flow of saline groundwater were studied. By established the seepage-freezing hydrothermal coupling calculation model, and combined with a small seepage-freezing model test, which based on the theory of heat transfer and seepage in porous media. Results show that the frozen wall is in an uneven state under the action of horizontal seepage. The frozen wall perpendicular to the direction of groundwater flow is formed slowly, while the frozen wall parallel to the direction of water flow is formed quickly. The salt content affects the development of the frozen wall. As the salt content increases, the thickness of the frozen wall decreases. The maximum percentage of reduction of the upstream and downstream frozen wall thickness can reach 80.4% and 59.5%, respectively. With the gradual expansion of the frozen wall around two freezing pipes, the flow around and the change of the flow velocity occur. The maximum value of the flow rate is about 3–4 times of the initial flow rate, and then the flow rate decreases rapidly until the frozen wall encloses. When the seepage velocity increases to 5.5 m/d and the salt content reaches 15‰ and above, the time for the closure of the frozen wall is significantly delayed or even impossible. The conclusions obtained in this study can provide a theoretical reference for the design and construction of the similar engineering.